A Randomized Controlled Trial Assessing the Impact of Opioid-Specific Patient Counseling on Opioid Consumption and Disposal After Reconstructive Pelvic Surgery. Issue 7 (July 2021) - Buono, Kristen; Whitcomb, Emily; Guaderrama, Noelani; Lee, Elizabeth; Ihara, Jun; Sudol, Neha; Lane, Felicia; Lee, Jennifer; Heliker, Bhumy Davé; Brueseke, Taylor
Abstract : (Abstracted from Female Pelvic Med Reconstr Surg 2021;27:151–158) Inappropriate overprescription of opioids, an important risk factor for the development of opioid abuse, has been demonstrated after benign hysterectomy and reconstructive surgery for pelvic organ prolapse. Several landmark studies have found that surgeons can prescribe fewer opioids in the postoperative setting without affecting patient distress or refill requests.